Evaluasi dan Perbaikan Desain Antarmuka Pengguna Situs Web Pattent Goods dengan Menggunakan Metode Goal-Directed Design (GDD) - Ardian Triantoro; Hanifah Muslimah Az-Zahra; Herman Tolle (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Pattent Goods is a local brand that presents comfortable daily wear products and focuses the production of socks located in Bandung, West Java. Pattent Goods has a website that needs to be improved in terms of interface appearance, information structure and content addition. The Goal-Directed Design method can provide solutions to create a website interface that fits the user. Goal-Directed Design (GDD) has six steps to research. The first stage is research to get initial data from general users and stakeholders. The second stage is modeling to produce persona modeling. The third stage is the requirements for finalizing the need for personas. The fourth stage is a framework for designing interface frameworks in the form of wireframes. The fifth stage is a refinement for the construction of a high fidelity prototype design. The last stage is support for running the final testing and evaluation of high fidelity prototype websites that have been improved. In the final evaluation using a System Usability Scale (SUS) questionnaire. The final evaluation result of system usability scale get an average score of 81.5 and get acceptable category in acceptability ranges, get category B in grade scale, get excellent category in adjcetive rating and percentile rank get grade A.